PARATE EKSEKUSI GROSSE AKTA PENGAKUAN HUTANG - Jamaluddin, Jamaluddin (AKTUALITA, 2011)
Grosse deed (Grosse deed of debt acknowledgment) is a deed madeunilaterally by the debtor in order to provide assurance to the debtor inform of an authentic deed or underhand deed. Grosse is a word whichmade in an authentic deed and has a legal power which is equivalent withthe criminal court decision which has a permanent legal force. Because ofthe Grosse deed contains a phrase âdivine justice on the one true Godâwhen the debtor defaults, the lender can be directly propose execution tothe court toward the object mentioned in the deed.Keywords: Execution, Grosse deed